If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 32 = -22 Reorder the terms: 32 + 6x = -22 Solving 32 + 6x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 6x = -22 + -32 Combine like terms: 32 + -32 = 0 0 + 6x = -22 + -32 6x = -22 + -32 Combine like terms: -22 + -32 = -54 6x = -54 Divide each side by '6'. x = -9 Simplifying x = -9
| 25x^2+20x+8=0 | | 10y+6-p=12p-3(p-2) | | x+15=3(x+2)-(2x-9) | | 6(d-4)+10= | | 25xy/35wxy | | -4(x+5)=12 | | 8(-23-5y)-6y=0 | | 6x-24=58+4x | | 8X+7X+15=90 | | 13x-8y=180 | | .7x-3.4=.6x+2.1 | | 11=-10+7m | | 20=-6y+4(y+3) | | 32x-4(8x+4)=16 | | 11/6x^4 | | -4x=3x+7 | | 5x+4(7)=3 | | -1=2+-0.5y | | 8X+7X+15=180 | | 15=5(4-x)+10 | | x^2+y^2+10x-4y+29=4 | | 5(23-4y)+4y=3 | | 8w-w+8w= | | m^2+4m-12=-7 | | (24p^14xq^18)^1/2 | | -1=2+-0.5 | | 12/2118/x | | y=4*tan(x) | | -11x+4=24 | | 600=.75x-(650+.5x) | | (66+30)*x=360+30*x | | 6×1/4 |